Att framställa det oframställbara. Stig Larssons poesi och det postmoderna - Niewiarowska-Rasmussen, Ewa (Folia Scandinavica Posnaniensia, 2007)
The paper constitutes an analysis of the poetry of Stig Larsson in the context of the postmodern break-up of traditional definitions of literary genres. The characteristic features of the Swedish poet's work are ambiguity, fragmentation, rich intertextual references, and, most importantly, a radically undefined, diffuse persona of the speaker, no longer able to organize the presented world. Larsson's poetry is rich in lexical, semantic and syntactic experimentation. The poet suggests a change in the relation between the author and the reader.